(untitled) (AACINI - International Journal of Industrial Engineering, 2023)
Organizational competitiveness arises from productivity, which occurs when companies use their resources efficiently to produce products and services that generate value for a customer at the lowest possible cost, which implies the use of tools such as those associated with the philosophy of lean manufacturing, which favor the elimination of actions that do not add value. That is why the objective of this project is to analyze the manufacturing process of fiberglass pangas in a company in the fishing sector, using lean manufacturing tools, to identify areas of opportunity that promote the improvement of organizational competitiveness. A SIPOC analysis of the panga base molding process was carried out, which served as the basis for developing the current value chain mapping (VSM) to identify the waste in said process. These wastes were sought to be eliminated with improvement proposals, and the result of the improved process was represented in a future state VSM, in which the cycle time was reduced by almost 50%. Finally, an action plan was structured for the implementation of these proposals, aligned with the strategic objectives of the company, since in this way, it can be more easily committed to the achievement of the established operational objectives when applying this type of tool, and see favored in all possible aspects.